Metabolomic Assessment Reveals Alteration in Polyols and Branched Chain Amino Acids Associated With Present and Future Renal Impairment in a Discovery Cohort of 637 Persons With Type 1 Diabetes - Tofte, Nete; Suvitaival, Tommi; Trost, Kajetan; Mattila, Ismo Matias; Theilade, Simone; Winther, Signe Abitz; Ahluwalia, Tarunveer Singh; Frimodt-Møller, Marie; Legido-Quigley, Cristina; Rossing, Peter (Frontiers in Endocrinology, 2019)
Background Improved understanding of the pathophysiology causing diabetic kidney disease is imperative. The aim of this study was to uncover associations between serum metabolites and renal outcomes. Methods Non-targeted serum metabolomics analyses were performed in samples from 637 persons with type 1 diabetes using two-dimensional gas chromatography coupled to time-of-flight mass-spectrometry. Longitudinal data at follow-up (median 5.5 years) on renal events were obtained from national Danish health registries. A composite renal endpoint (n=123) consisted of estimated glomerular filtration rate(eGFR) decline from baseline (≥30%), progression to end-stage renal disease and all-cause mortality. Metabolites with significant associations (p<0.05) in any of the cross-sectional analyses eGFR and albuminuria were analysed for either specific or composite endpoint. Adjustments included traditional cardiovascular risk factors and correction for multiple testing. Results A data-driven partial correlation analysis revealed a dense fabric of co-regulated metabolites and clinical variables dominated by eGFR. Ribonic acid and myo-inositol were inversely associated with eGFR, positively associated with macroalbuminuria (p<0.02) and longitudinally associated with higher risk of eGFR decline ≥30%, (HR 2.2-2.7, CI [1.3-4.3], p<0.001). Ribonic acid was associated with a combined renal endpoint (HR 1.8, CI [1.3-2.3], p=0.001). The hydroxy butyrate 3,4-dihydroxybutanoic acid was cross-sectionally associated with micro- and macroalbuminuria, urinary albumin excretion rate and inversely associated with eGFR (p<0.04) while branched chain amino acids were associated with eGFR and lower risk of the combined renal endpoint (p<0.02). Conclusions Alterations in serum metabolites, particularly polyols and amino acids, were associated with renal endpoints in type 1 diabetes highlighting molecular pathways associated with progression of kidney disease. External validation is needed to further assess their roles and potentials as future therapeutic targets.